13C NMR assignments of regenerated cellulose from solid-state 2D NMR spectroscopy. (20th October 2016) - Idström, Alexander; Schantz, Staffan; Sundberg, Johan; Chmelka, Bradley F.; Gatenholm, Paul; Nordstierna, Lars
Highlights: 13 C-enriched cellulose II was analyzed by solid-state 2D NMR spectroscopy. Four conformationally different anhydroglucose units were observed for cellulose II. Two were assigned to crystalline parts, two were assigned to non-crystalline parts. Spectral deconvolution of C1, C4, and C6 regions of cellulose II were accomplished. Abstract: From the assignment of the solid-state 13 C NMR signals in the C4 region, distinct types of crystalline cellulose, cellulose at crystalline surfaces, and disordered cellulose can be identified and quantified. For regenerated cellulose, complete 13 C assignments of the other carbon regions have not previously been attainable, due to signal overlap. In this study, two-dimensional (2D) NMR correlation methods were used to resolve and assign 13 C signals for all carbon atoms in regenerated cellulose. 13 C-enriched bacterial nanocellulose was biosynthesized, dissolved, and coagulated as highly crystalline cellulose II. Specifically, four distinct 13 C signals were observed corresponding to conformationally different anhydroglucose units: two signals assigned to crystalline moieties and two signals assigned to non-crystalline species. The C1, C4 and C6 regions for cellulose II were fully examined by global spectral deconvolution, which yielded qualitative trends of the relative populations of the different cellulose moieties, as a function of wetting and drying treatments.